The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1038/cddis.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

ATM-NFκB axis-driven TIGAR regulates sensitivity of glioma cells to radiomimetics in the presence of TNFα

Abstract: Gliomas are resistant to radiation therapy, as well as to TNFα induced killing. Radiation-induced TNFα triggers Nuclear factor κB (NFκB)-mediated radioresistance. As inhibition of NFκB activation sensitizes glioma cells to TNFα-induced apoptosis, we investigated whether TNFα modulates the responsiveness of glioma cells to ionizing radiation-mimetic Neocarzinostatin (NCS). TNFα enhanced the ability of NCS to induce glioma cell apoptosis. NCS-mediated death involved caspase-9 activation, reduction of mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…As suppressing glycolysis with inhibitors was not effective at killing tumor cells, its combination with other tumor-specific metabolic inhibitors may be necessary for therapeutic intervention [32]. Silencing TIGAR also enhanced the radiosensitivity of U87MC and glioma cells [13]. Our findings suggest that combining glycolytic inhibitors with a potential TIGAR inhibitor and current standard chemotherapy may be a powerful and effective treatment for not only human leukemia but also other cancer types.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As suppressing glycolysis with inhibitors was not effective at killing tumor cells, its combination with other tumor-specific metabolic inhibitors may be necessary for therapeutic intervention [32]. Silencing TIGAR also enhanced the radiosensitivity of U87MC and glioma cells [13]. Our findings suggest that combining glycolytic inhibitors with a potential TIGAR inhibitor and current standard chemotherapy may be a powerful and effective treatment for not only human leukemia but also other cancer types.…”
Section: Discussionmentioning
confidence: 95%
“…A number of genetic alterations seen in CN-AML patients with possible prognostic relevance (DNMT3A, IDH1/2, TET2) are not considered here, and the correlation of TIGAR expression and outcome may not be independent of other variables in CN-AML. In addition, TIGAR knockdown enhanced the radiosensitivity of cancer cells, suggesting that correlation of TIGAR expression and outcome of patients with CN-AML may also depend on the response of AML cells to chemotherapy [13]. In the future, it will be important to understand how TIGAR affects the response of leukemia cells to chemotherapy or targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Five housekeeping genes were included on the array (B2M, HPRT1, RPL13A, GAPDH and ACTB) to normalize the transcript levels. Results were analyzed as per user manual guidelines using integrated web-based software package for the PCR Array System (RT2 Profiler PCR Array Human Glucose Metabolism PAHS-006Z).…”
Section: Methodsmentioning
confidence: 99%
“…However, navigation of the role of altered ATM gene in brain tumors seems to be too limited and has been restricted to few types of tumors such as glioma. In the recent study, the molecular mechanisms behind the resistance to radiotherapy were explored in glioma cells [14]. It was found that ATM expression plays important role in radioadaptive nature of glioma cells in cooperation with a network of other prosurvival proteins.…”
Section: Introductionmentioning
confidence: 99%